Study of Geometric Modification of Calciner in Cement Plant - Prihadi Setyo Darmanto; Muhammad Isroffi (Mesin, 2023)
Suspension preheater is a raw mix pre-heating equipment used in a cement plant. The heat is used to raise raw mix temperature up to 800 0C -900 0C. The process results in an 80-90% degree of calcination. In this project, an increasing percentage of calcination in suspension preheater and reducing the load in the kiln is attempted, by including the calciner in suspension preheater. This project will focus on a suspension preheater system with a separate line calciner (SLC) at Cement Plant with 5000 ton per day (TPD) capacity. Calciner in existing conditions will be modified by extending its length by 2.5 m. Computational fluid dynamics (CFD) method was chosen to simulate the performance of the calciner. The results show that the alternative design can increases calcination percentage up to 76,32%, from the original value of 71%. The heat transfer on the alternative design also increases by 9%. As a result, the temperature output of the cyclone 5 also decreases, reducing the heat consumption. Another consequence of the alternative design is the possibility to increase the production capacity while maintaining the outlet temperature of cyclone 5, by increasing raw mix feeding without additional fuel consumption. Thus, clinker production can be increased by 8%.